Estructura organizacional y relaciones con el entorno socioeconómico de la Universidad San Gregorio de Portoviejo y Universidad Técnica de Manabí para la transferencia de conocimiento científico-tecnológico - Murillo Basurto, Cruz Jessenia (2020)
The main objective of the research was to carry out a study of the organizational Structure and relations with the socioeconomic environment of the San Gregorio University of Portoviejo and the Technical University of Manabí for the trnasfer of scientific-technological knowledge, in order to obtain the pertinente information in the progress of the investigation, three phases were carried out in the methodological development, in the first, the organizational structure of the institutions was analyzed, for which the technique of interviewing people from the research and linkage departments of the universities and Surveys to the research professors of the same, the second phase allowed to identify the companies benefited with the transfer of knowledge through the research and linkage projects executed by the universities, with this objetive the analytical methods were carried out when studying the information obtained and synthetic for the realization from a summary table, in the third phase, the relevance of knowledge trnsfer could be determined. In conclusión, the organizational Structure is the basis in the development of the university´s subsstantive functions, thus positively or negatively influencing its operation, so resources should be directed towards improving academic productivity